The Impact of Forestry on The Economy of The State of Azad Jammu and Kashmir - Nasim Akhter; Sabahat Akram; Bashir Ahmed Khilji; Shahid Hussain (European Scientific Journal, ESJ, 2016)
In this paper a study was carried out to assess the contribution and impact of forestry resource on the economy of the State of Azad Jammu & Kashmir, as 42% of the total area is covered by forests. To conduct the study both secondary and primary data was used. Secondary data was collected from different public sector concerned departments. Primary data was collected through a comprehensive questionnaire from 212 selected respondents by using convenience sampling of 3 Forest Divisions which were 16% of total targeted population. Multiple Regression Model was applied by using last twenty years secondary data of ten sectors of the economy. The value indicates goodness of fit of the model. The results show that forestry resources are an important contributor to the state’s National Income. The study recommends concerted efforts and integrated policy making to conserve the fragile eco system of mountainous areas like AJK. The primary and secondary data reveals that 16000 people are availing job opportunities through forestry resource.